Evolutionary Game Research on Stakeholder Decision-Making in Preprint Platform - LI Huimiao, NIU Xiaohong, MA Zhuo, GUO Mohan (Nongye tushu qingbao xuebao)
[Purpose/Significance] With the globalization of knowledge sharing and the vigorous development of preprint at home and abroad, the role of preprint platform in academic exchange has been recognized and appreciated by academic community. This paper introduces the evolutionary simulation method for the first time from the previous research on government and enterprises to the research on preprint platform, and takes the three main stakeholders in the construction of preprint platform, that is government, researcher and the public as the main players of the game. Different from the existing research, this paper uses system dynamics theory and software to fill the gap in quantitative analysis of SD model, and combines qualitative and quantitative research to further enrich the research content of the preprint platform through game model construction and simulation analysis. This research aims to guide stakeholders to actively participate in the construction of preprint platform, improve the utilization rate of domestic preprint platform by users, and promote the construction of preprint platform in China. [Method/Process] This study established a tripartite evolutionary game model of "government, researcher, and the public" to analyze the strategic stability of the three stakeholders. Vensim PLE software was used to simulate and analyze the the SD model, focusing on the influence of mixed strategies and external sensitivity variables on stakeholders' decision behavior. [Results/Conclusions] In the construction of preprint platform, the willingness of government supervision is mainly influenced by the supervision cost and credibility Within a reasonable range, the higher the scientific research funding for researchers or the more severe the penalty for their passive participation, the greater the willingness of researchers to participate actively. The public's willingness to cooperate is influenced by the costs of participation and the social dividends. In the future, the construction of the preprint platform can be continuously promoted from three perspectives: formulating the framework of the underlying reward and penalty mechanism of the preprint platform, establishing the reputation evaluation mechanism of researchers, and accelerating the construction of the government's open scientific innovation service. However, due to the limitation of the author's professional ability, the cognition of the preprint platform and the consideration of the relevant policy establishment process are relatively limited. There are many stakeholders involved in the construction of preprint platform, and there are also many factors that can affect the decision-making behavior in the external environment and system. In this study, three stakeholders from three main aspects are selected to model and study the external influence. In the future, we can select stakeholders from different angles and increase the influencing factors to expand the research on preprint platform.